2020
DOI: 10.3390/foods9040434
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antioxidant and Enzymes (A-Amylase and B-Glucosidase) Inhibitory Activity of Morinda lucida and Momordica charantia Leaves from Benin

Abstract: Background: Momordica charantia Linn. (Cucurbitaceae), the wild variety of bitter melon and Morinda lucida Benth (Rubiaceae) were commonly used as a popular folk medicine in Benin. This research focused to measure the antioxidant and enzyme inhibitory effects of M. charantia and M. lucida leaves and their antidiabetic activity. Methods: Antioxidant activities were evaluated by micro-dilution technique using DPPH free radical scavenging activity and β-carotene-linoleate bleaching assay. The α-amylase inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…It was evaluated by the methodology as described previously [ 27 ] with a few modifications. Five serial diluted concentrations (0.312 to 5 mg/ml) of the plant extract (500 μl) and 500 μl of porcine pancreatic amylase solution (0.5 mgml − 1 in 0.02 M PBS with 6.9 pH having 0.006 M NaCl) was poured and incubated for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It was evaluated by the methodology as described previously [ 27 ] with a few modifications. Five serial diluted concentrations (0.312 to 5 mg/ml) of the plant extract (500 μl) and 500 μl of porcine pancreatic amylase solution (0.5 mgml − 1 in 0.02 M PBS with 6.9 pH having 0.006 M NaCl) was poured and incubated for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, many researches confirmed that the phenolics and saponins (e.g. gallic acid, p-coumaric acid, chlorogenic acid, tannic acid, rutin, naringin, quercetin, epicatechin (-), genistein, naringenin and daidzein) distributed in various M. charantia tissues including leaves [20][21][22]. Diaz-de-Cerio et al studied about polar compounds in guava leaves, they found 13 ellagic and gallic acid derivatives, quercetin and its derivatives, catechin, gallocatechin, gallic acid, naringenin and many guavinosides [17].…”
Section: Plos Onementioning
confidence: 99%
“…The IC 50 values were graphically determined by plotting the inhibition percent against inhibitory concentration. The antioxidant activity index (AAI) was calculated using following formula: [ 23 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The gradient elution was from 2% to 100% B at 30 °C for 60 min, and the elution flow was set at 1000 µL/min. Further, 300 nm analytical wavelength was used for detection in accordance with the literature [ 42 ].…”
Section: Methodsmentioning
confidence: 99%